2020
DOI: 10.1111/eva.13124
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐genome SNP markers reveal conservation status, signatures of selection, and introgression in Chinese Laiwu pigs

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 84 publications
6
20
1
Order By: Relevance
“…To identify the genomic regions with high ROH frequency, we first calculated the frequency of SNP occurrence in the ROH and selected the top 1% among those with the highest frequency (present in at least 33.3% of the samples) ( Figure 3 ). There were four adjacent SNPs on SSC4 at ∼35 Mb with the highest frequency of 60.2%, which is similar to the findings of Wang et al (2021) , but no gene has been mapped in this region according to the reference genome (Sscrofa11.1). Neighboring selected SNPs that constitute regions with the highest frequency of ROH are called ROH islands.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…To identify the genomic regions with high ROH frequency, we first calculated the frequency of SNP occurrence in the ROH and selected the top 1% among those with the highest frequency (present in at least 33.3% of the samples) ( Figure 3 ). There were four adjacent SNPs on SSC4 at ∼35 Mb with the highest frequency of 60.2%, which is similar to the findings of Wang et al (2021) , but no gene has been mapped in this region according to the reference genome (Sscrofa11.1). Neighboring selected SNPs that constitute regions with the highest frequency of ROH are called ROH islands.…”
Section: Resultssupporting
confidence: 73%
“…The average H o and H e of this Laiwu pig population were 0.27 and 0.38, respectively. The value of H o is lower than the result reported before (0.284), whereas H e is higher (0.281) ( Wang et al, 2021 ). In addition, the N e of this population was 52.6, which suggests it is quite likely that inbreeding has happened.…”
Section: Resultscontrasting
confidence: 70%
“…Chinese and EUR pigs in the population structure analysis. Interestingly, LWH pig breed is one of Chinese local pig breed classi ed to NCN also investigated here, which proved to have genetic components introgressed from EUR pigs [52], which supported by genetic evidence and historical evidence that EUR pigs were then introduced to the Shandong province and crossed with local breeds during the colonization of Yantai and Qingdao cities of Shandong Province by Britain and Germany at the early 20th century. Similarly, for PDW, EUR pigs such as Yorkshire were introduced to the Shanghai and crossed with local breeds subsequently since the Opium War with the opening of Shanghai [15].…”
Section: Discussionsupporting
confidence: 72%
“…Selection may strongly affect the distribution of ROH, and regions of genomic loci under selection tend to generate a high frequency of ROH (hotspots) (5). An increasing number of studies have confirmed that ROH hotspots are due to positive selection for economically important traits in cattle (6,7), pigs (8)(9)(10), chickens (11,12), goats (13,14), and sheep (15,16). Therefore, the identification and characterization of ROH in a population can provide new insights for uncovering the demographic history and the genetic basis of germplasm characteristics.…”
Section: Introductionmentioning
confidence: 99%